THE INFLUENCE OF INNOVATIVE TECHNOLOGIES ON THE DYNAMICS OF LAND USE INDICATORS OF UKRAINIAN AGRICULTURAL ENTERPRISES - Iryna MATVIEIEVA; Valentyna GROZA; Nataliia ISCHCHENKO; Nataliia KOMAROVA; Liliia SKRYPNYK; Tatyana PRIADKA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article examines the innovative activities of agricultura lenterprises on the territory of Ukraine, in particular the use of unmanned aerial vehicles (DJI Agras T30 multicopter). The policy of the leading Ukrainian company Ukrland farming in the field of balanced land use and effective development of the agro-industrial complex was studied. The criteria used in the development of the plant nutrition system have been formed. Advantages were formed in the performance of works on the application of nutrients and plant protection with the help of the Agras T30 multicopter. Proposals were made to increase the level of resource-saving activities of agro-industrial complexes due to the use of alternative methods of agricultural production, namely organic farming, biointensive mini-farming, biodynamic farming, ecological agriculture, EM technologies, established agriculture with low resource intensity, precision agriculture. The existence of an economic-mathematical model of the influence of the use of innovative technologies, in particular, the use of the DJI Agras T30 multicopter, on the dynamics of indicators of the efficiency of the cultivation of cultivated areas of agricultural enterprises has been formed and substantiated.